2003
DOI: 10.1051/0004-6361:20030129
|View full text |Cite
|
Sign up to set email alerts
|

Shakhbazian compact galaxy groups

Abstract: Abstract. The results of the redshift measurements and of the detailed surface photometry in BVR of the compact group ShCG 376 are presented. The radial velocity dispersion, the virial mass, the total luminosity, the M/L ratio, and the crossing time of the group are estimated. The group consists of eight accordant redshift spiral galaxies. Four (or possibly five) of the group members have emission-line spectra. Such morphological content and the number of emission-line galaxies are very atypical for compact ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 23 publications
7
49
1
Order By: Relevance
“…Tovmassian et al 1999). The similarity of the axial ratio distribution and its mean value between the original HCGs and the sample of HCG + environment systems studied here and in the work of Tovmassian & Chavushyan (2000) suggests that the HCG + environment systems also have a prolate-like shape.…”
Section: Correlation Of Velocity Dispersion Number Of Group Memberssupporting
confidence: 58%
See 1 more Smart Citation
“…Tovmassian et al 1999). The similarity of the axial ratio distribution and its mean value between the original HCGs and the sample of HCG + environment systems studied here and in the work of Tovmassian & Chavushyan (2000) suggests that the HCG + environment systems also have a prolate-like shape.…”
Section: Correlation Of Velocity Dispersion Number Of Group Memberssupporting
confidence: 58%
“…Tovmassian et al (1999) show that the velocity dispersion of HCGs correlates with their projected shape: the lower the group's projected axial ratio, the smaller its velocity dispersion. They conclude that member galaxies move in radial orbits predominantly along the group's elongation.…”
Section: Introductionmentioning
confidence: 93%
“…They were selected as dense groups of mainly red galaxies, the images of many of which were often hard to distinguish from those of stars. Through follow-up spectral observations (Tiersch et al 2002, hereafter Paper I;Tovmassian et al 2003a, hereafter Paper II, 2003b, hereafter Paper III, 2004a, hereafter Paper IV, 2004b, hereafter Paper V) it was found that some objects in the area of groups which were assumed in original papers to be stars, are in reality galaxies. On the other hand, only a Figures 1 and 3-10 are only available in electronic form at http://www.edpsciences.org few assumed members of ShCGs turned out to be stars.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study of 13 ShCGs are presented in Tiersch et al (2002, Paper I), and in Tovmassian et al (2003a, Paper II, 2003b. In this paper we present the results of the study of ShCG 181, ShCG 344, ShCG 361, and ShCG 362.…”
Section: Introductionmentioning
confidence: 99%